CERPEN MALING KARYA KOMANG ADNYANA ANALISIS STRUKTUR NARATOLOGI GERARD GENETTE - I Wayan Juliana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The short story Maling by Komang Adnyana is one of several short stories in the Metek Bintang short story collection. The themes raised in the collection of short stories by Metek Bintang are interesting and unexpected, because it is rare for themes such as transgender, LGBT, and even the theme of selling children to appear in modern Balinese literature. The themes that adorn modern Balinese literature are themes of teenage romance, social criticism, polemics on inter-caste marriages, love of Balinese Caucasians, and others. In this paper, we will examine a short story entitled Maling. The short story of Maling will be analyzed based on Gerard Genette's narrative theory which focuses on narrative order which refers to an attempt to tell an event. The result of this paper is to describe the plot chronologically and logically based on the main function in the short story.Keywords: Short story, Narrative, structure, narratology, modern Balinese literature